A COMPARATIVE ANALYSIS OF TASK-BASED LANGUAGE TEACHING (TBLT) CRITERIA IN COURSE BOOKS FOR UPPER INTERMEDIATE ENGLISH STUDENTS - Saiful Akmal (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
Recently, the importance of task-based language teaching (TBLT) is presumably clear and therefore has also widely being used in many countries. The process of recognizing a ‘task’ itself could be one of the fields where it tends to be slightly fuzzy, especially for a new, learner and inexperience teacher. Many English experts and task-based supporters have published various books to assist their ideas. Perhaps that is why; we now have had different criterion of assessing a ‘task’. This paper thus, intends to establish the extent to which a modern course book has encompassed principles and practice of TBLT when compared with older books. I have therefore taken two books as the source of data for this paper; Natural English-Upper Intermediate Student’s Book and Workout Upper Intermediate Student’s Book, both aimed at the same language level of learner. Both are intended to upper intermediate student.